STUDI KARAKTERISTIK TANAMAN GUMI BANTEN UNTUK LANSEKAP POHON TEPI JALAN - Sukewijaya, I Made; Kohdrata, Naniek (Bumi Lestari, 2016)
Gumi Banten plants are Balinese local plants that have social-religius function and apotential for roadside tree planting as well. Combining the roadside landscape plantingcriteria with the concept of Gumi Banten plants conservation is an effort to maintain thegenius loci of the Balinese culture within the human functionality living context of presentand future. The trees selection is done in two stages. The first focuses on trees structure andcharacteristics that safe for the use of roadside landscape planting. This first stage resultedin 13 trees out of 72 types of trees that had been identified in the book of EnsiklopediTanaman Gumi Banten. The second stage is for analysing the trees potential from the spatialfunction perspective on which a road is located. There are three aspects of roadside treelandscaping potential for this study that are ornamental, view guiding, and shelter.
Keywords: roadside landscape, gumi banten plants